Public ICT center for rural development inclusiveness, sustainability, and impact. (Asian Development Bank, 2017)
Cybercafes arise as small urban businesses but are not financially viable in rural areas. Telecenters are a governmental response, modeled after cybercafes, to try to bring the benefits of computers and the internet to underserved rural communities.This report discusses why ICT centers remain popular with governments and rural people, and why it is difficult to serve rural areas. Effective public support practices are identified, based on a review of the record of experience, with special reference to two case studies: a government run initiative in the Philippines and a public private partnership in Sri Lanka.